Preventive start‐time optimisation of open shortest path first link weights for hose model. Issue 2 (1st June 2014) - Sandaruwan Ranaweera, Ravindra; Mohammad Kamrul, Islam; Oki, Eiji
Abstract : Optimising link weights in an open shortest path first network is a challenging traffic engineering problem to reduce network congestion. Most of the previous studies have focused on the application of start‐time optimisation (SO) and run‐time optimisation on both pipe and hose models of link weight optimisation. In a more recent study, an efficient policy, preventive start‐time optimisation (PSO), has been introduced for link weight optimisation. However, no studies have been reported on the application of PSO to the hose model where the exact traffic demand between each source and destination node pair does not need to be specified. A PSO policy for the hose model to optimise the link weights against link failures is proposed. The proposed scheme employs a heuristic algorithm to determine a suitable set of link weights to reduce worst‐case congestion for any single link failure. It efficiently selects the worst‐case performance traffic matrix and reduces the worst‐case congestion ratio as compared with a brute‐force scheme which is computationally expensive when searching the link weight space against all the possible traffic matrices and topologies created by single link failures. The numerical results show that the proposed scheme is more effective in the reduction of worst‐case congestion ratio than the scheme utilising SO.